Heterotopic Pregnancy: A Challenge in Early Diagnosis - Karkee, Roman; Sharma, Amit; Dangal, Binod (Journal of Nepal Health Research Council, 2019)
Heterotopic pregnancy is the simultaneous existence of intrauterine and extrauterine gestation. It is usually seen in women at risk for ectopic pregnancy or those undergoing fertility treatments. The incidence has dramatically risen to 1 in 3900 of pregnancies via assisted reproductive techniques or ovulation induction, compared to 1 in 30000 of spontaneous conception. Besides this, history of pelvic inflammatory disease (PID), tubal damage, pelvic surgery and prior tubal surgery can increase its risk. Here we present a case of heterotopic pregnancy which was diagnosedafter ectopic gestation ruptured along with compromised intrauterine gestation and maternal condition. Earlier diagnosis before this life-threatening event could have saved the intrauterine fetus.Keywords: Extrauterine pregnancy; heterotopic pregnancy; ruptured ectopic.